SHARIAH GOVERNANCE DAN KUALITAS TATA KELOLA PERBANKAN SYARIAH - Ali Rama; Yella Novela (Signifikan: Jurnal Ilmu Ekonomi, 2015)
Corporate governance for Islamic banking has a unique feature compared with banking conventional. It is required to complement the existing governance framework with shariah governance system to ensure the shariah compliance of all Islamic banking’s operational. Therefore, this study aims to analyze the effect of the practice of shariah governance to the quality of GCG implemented by Islamic banks. Practices of shariah governance are measured by number of shariah board members, doctoral qualification of shariah board and frequency of shariah board meeting. The study finds that shariah governance has a significant impact to the increase quality of GCG in Islamic banks. Another interesting finding is that the increase of credit risk (NPF) leads to the worse of Islamic banks’ corporate governance. ROA and CAR have no significant effect to the quality of corporate governance in Islamic banks. The study recommends that the Islamic banks should improve their shariah governance practices in order to increase their governance performance as well as public confidenceDOI: 10.15408/sjie.v4i2.2301